Refractory Auto-Immune Thrombotic Thrombocytopenic Pupura Successfully Treated With Caplacizumab - Mellaza, Chloé; Henry, Nicolas; Fayolle, Pierre-Marie; Mortaza, Satar; Subra, Jean-François; Veyradier, Agnès; Coppo, Paul; Augusto, Jean-François (Frontiers in Medicine, 2020)
Thrombotic thrombocytopenic purpura (TTP) is a rare thrombotic microangiopathy characterized by mechanical hemolytic anemia, profound thrombocytopenia, and neurological manifestations. Acquired auto-immune TTP, the most prevalent cause of TTP, is induced by the presence of inhibitory anti-ADAMTS13 auto-antibodies. Modern treatment of acquired TTP relies on plasma exchange, rituximab, and steroids. Caplacizumab (Cablivi®), a humanized single-variable domain immunoglobulin that targets the A1 domain of the ultra-large von Willebrand factor, inhibits the interaction between ultra-large vWFand platelets. In two clinical trials, caplacizumab, in addition to conventional treatment, shortened the delay to platelet count normalization in comparison to conventional treatment plus placebo, without increasing significantly hemorrhagic complications. Moreover, caplacizumab was associated with reduced occurrence of a secondary endpoint associating death, TTP recurrence, and major thromboembolic events. Here, we report the off-label use of caplacizumab in a 68-year-old patient with confirmed acquired TTP, severe thrombocytopenia, and generalized tonic–clonic seizures requiring mechanical ventilation and admission in the intensive care unit. Conventional treatment was rapidly started. Despite the intensification of plasma exchange treatment with twice-daily sessions, steroid continuation, and a second rituximab infusion on day 6, thrombotic microangiopathy worsened with thrombocytopenia at 21 g/L on day 8 from admission. We also considered using caplacizumab, which we could obtain and start on day 12 from admission, as it was available under a temporary authorization use in France. As soon as 12 h after caplacizumab initiation, we observed a significant increase of platelet count and improvement of other hemolytic parameters. We observed resolution of encephalopathy and complete recovery of motor paralysis, allowing us to stop mechanical ventilation on day 14. Caplacizumab was maintained for 128 days until day 139 from initial admission. The patient is going well 10 months after initial admission, without any neurological sequelae, and TTP did not relapse. To the best of our knowledge, this is the first reported use of caplacizumab in such a condition. This case report suggests that caplacizumab use may help to reduce the rate of refractory TTP episodes.